ASAL USUL PANGERAN MENANG JAGAD DAN RATU MINAK KEMALA DI KAMPUNG NEGARA BATIN, KABUPATEN WAY KANAN - Prasetyo, Nereus Eko; Sahmega, Bagus; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research is about the origin of Pangeran Menang Jagad and Minak Kemala in Kampung Tua, Negara Batin District, Way Kanan Regency. The formulation of the problem of "How is the Origin of Prince Menang Jagad and Minak Kemala in Kampung Tua, Negara Batin District, Way Kanan Regency?". The purpose of this research is to add insight into the origin of Pangeran Menang Jagad and Minak Kemala in Kampung Tua, Negara Batin Subdistrict, Way Kanan Regency. The research method uses qualitative research ethnographic studies. From the folk stories known in the community of Kampung Tua, Negara Batin District, Way Kanan Regency, Pangeran Menang Jagad and Minak Kemala have a very important role in enriching their cultural heritage and local identity. The story of Prince Menang Jagad and Minak Kemala is not just a love story, but also a reflection of the values, wisdom and courage valued in the local community. Their origins are part of the myths and legends told through generations in the Kampung Tua community. Their legendary love story is a source of inspiration and learning for the younger generation about values such as loyalty, cooperation and courage in the face of challenges.